Ballistic impact response of a fluid/structure coupling-based modification of human thorax modelling. (July 2021) - Gilson, L.; Rabet, L.; Imad, A.; Nsiampa, N.; Coghe, F.
Abstract: Studying the mechanical response of the human thorax submitted to ballistic impact is a challenging field of research. For ethical reasons, it is not possible to perform tests on the human body. Numerical simulations are therefore one of the alternatives for evaluating the mechanical response of the human thorax. In earlier research, a simplified human thorax submitted to low-velocity impacts without ballistic protection was modelled. Not all internal organs in the thorax were taken into account. The only considered organs were the heart, lungs, trachea and aorta, with the space between them being void. The organs were covered by an idealised structure simulating the rib cage, spine and muscles. Such a simplified model was however sufficient in the field of less-lethal impact assessment. Indeed, in this case, only forces and displacements are taken into account. In the field of behind armour blunt trauma (BABT), spherical pressure or shock waves are expected to appear and propagate into internal organs. Nevertheless, the presence of the void space makes it impossible to evaluate the propagation of the considered waves. This paper focuses on a method for filling the void space and making the model more comprehensive. Starting from the initial meshed geometry of this simulated thorax, it uses a coupling between Lagrangian and arbitrary Lagrangian-Eulerian (ALE) objects. Finally, the use of the filled model is extended to a BABT case study. From the simulations, it could be concluded that BABT should be related to "blast" instead of "viscous" solicitations.